2020
DOI: 10.13106/jafeb.2020.vol7.no12.869
|View full text |Cite
|
Sign up to set email alerts
|

The Prominence of Financial Considerations on Housing Investors’ Purchase Decisions

Abstract: As a basic element for sustainable development, the residential housing industry is vital and fundamental for every country in the world. Therefore, this study examines the impacts of financial considerations on house purchase decisions by housing investors in Auckland, New Zealand. 110 completed questionnaires were statistically analyzed. For testing the proposed hypotheses, Structural Equation Modelling (SEM) was used. The results show that house prices, income, and credit accessibility significantly influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It means that employees' capacity to deliver on customer expectations as well as their capacity to fortify customer relationships determines how effectively brand equity performs. Previous research has found that the emergence of high-quality staff behaviour has a significant impact on retail customer trust [60]. Personnel behaviour had a positive impact on customer trust, which was relevant to previous studies.…”
Section: Staff Behavioursupporting
confidence: 53%
“…It means that employees' capacity to deliver on customer expectations as well as their capacity to fortify customer relationships determines how effectively brand equity performs. Previous research has found that the emergence of high-quality staff behaviour has a significant impact on retail customer trust [60]. Personnel behaviour had a positive impact on customer trust, which was relevant to previous studies.…”
Section: Staff Behavioursupporting
confidence: 53%
“…The study proposes that the government should closely monitor the implementation of the affordable housing policy to improve the quality of housing for the people. Dananjoyo et al (2020) examine the impacts of financial considerations on house purchase decisions by housing investors in Auckland, New Zealand. In this study, Structural Equation Modelling (SEM) was used with 110 completed questionnaires.…”
Section: Theoretical Basicmentioning
confidence: 99%
“…Moreover, only limited study examines service quality as a critical factor influencing housing provision. Previous study discussed about the importance of service excellence when developers constructing a client house [8]. Therefore, the gap of this research is there is no research about sustainable service quality in the residential housing industry.…”
Section: Introductionmentioning
confidence: 95%
“…Housing is described as the primary needs that should provide cosines for the homeowner [4]. Once a homeowner has willingness to purchase a house, they should consider many factors such as housing design [5], location [6], reputation of the property developer [7], financial considerations [8]. Moreover, only limited study examines service quality as a critical factor influencing housing provision.…”
Section: Introductionmentioning
confidence: 99%